Bullying Behavior of High School Students in the School Environment - Aprilia, Devi (Journal of Educational Studies, 2023)
Bullying behavior in the school environment can create an environment that is less supportive of student development, both in the academic and social fields. Bullying behavior can hurt students, leaving them feeling unwanted and rejected by their environment. This will certainly have an effect on various student activities at school. Researchers took the title "Bullying Behavior of High School Students in the School Environment". With the formulation of the problem studied, namely "How is the bullying behavior of high school students in the school environment of SMK Negeri 1 Masbagik ". The author uses a descriptive research method of case study type. Research with the type of case study aims to know about something in depth. Descriptive research is concerned with collecting facts and data validly to provide an overview of the object under study. During the school years, bullying is one of the most common expressions of violence in a peer context. Research on bullying began more than forty years ago, when the phenomenon was defined as 'aggressive and deliberate acts committed by a group or individual repeatedly and over a period of time against a victim who cannot easily defend himself'. There are three relevant criteria for defining aggressive behavior as bullying: (1) repetition, (2) intentionality, and (3) imbalance of power. Given these characteristics, bullying is often defined as the systematic abuse of power by peers. It is recognized globally as a complex and serious issue. In this paper, we discuss its prevalence, age and gender differences, and different types of oppression, as well as why it occurs and how long it lasts, ranging from large surveys conducted in western countries and to a lesser extent in lower countries. - and middle-income countries. Prevalence rates vary widely between studies; Therefore, special attention will be paid to the definition, time reference period and frequency criteria. We will also focus on risk factors as well as the short- and long-term impacts of bullying and victimization. Lastly, one section will be dedicated to reviewing what is known about effective bullying prevention.